Description of Rheumatoid Arthritis Pain and Level of Independence in Daily Life Activities in the Elderly in the Working Area of the Kaluku Bodoa Makassar Health Center - Magdalena, Magdalena (Journal of Asian-african Focus in Health, 2023)
The elderly are a high-risk group who experience various health problems, especially degenerative diseases such as Rheumatoid Arthritis. Rheumatoid Arthritis has developed and attacked 2.5 million Europeans, around 75%, the prevalence of rheumatic pain in Indonesia reaches 23.6% to 31.3% . This study aims to determine the description of rheumatoid arthritis pain and the level of independence in daily life activities in the elderly in the Kaluku Bodoa Health Center Makassar Working Area . The population in this study were all elderly people in the working area of the Kaluku Bodoa Makassar Community Health Center. The number of samples studied was 67 respondents using the accidental sampling technique . Data was collected from March 30 to April 11 through filling out questionnaires and structured interviews . The results showed that of the 67 respondents, the majority of respondents experienced mild pain, namely 51 people (76.1%), while the level of independence of the elderly in daily life , the majority of respondents were independent, namely 48 people (71.6%) in perform ADL (Activity Daily Living). Based on the research results, it was concluded that respondents who experienced severe pain would always depend on their family members, thereby interfering with their daily activities, while respondents who only experienced mild pain would be more independent and able to carry out their daily life activities without help from other people . It is hoped that it can provide support to elderly families so that they continue to participate in the elderly posyandu program, as well as providing health education related to the elderly, such as rheumatoid arthritis pain for the elderly.